1998
DOI: 10.1074/jbc.273.45.29481
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast RAD7 and RAD16 Genes Are Required for Postincision Events during Nucleotide Excision Repair

Abstract: In eukaryotes, nucleotide excision repair (NER) is a complex reaction requiring multiple proteins. In the yeast Saccharomyces cerevisiae, two of these proteins, Rad7 and Rad16, are specifically involved in the removal of lesions from transcriptionally silent regions of the genome in vivo. Extracts prepared from rad7 or rad16 mutant cells are deficient, but not totally defective, in both oligonucleotide excision and repair synthesis of damaged plasmid DNA. We show that these extracts are, however, fully profici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…in the very initial step of damage recognition in cooperation with NEF2 as shown in our studies here and also in the post-incision phase (23), perhaps in the turnover of the incision protein machinery, and in the recruitment of factors to perform the DNA repair synthesis reaction.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…in the very initial step of damage recognition in cooperation with NEF2 as shown in our studies here and also in the post-incision phase (23), perhaps in the turnover of the incision protein machinery, and in the recruitment of factors to perform the DNA repair synthesis reaction.…”
Section: Discussionsupporting
confidence: 71%
“…Recent studies have suggested an involvement of the Rad7 and Rad16 proteins in the post-incision phase of NER (23).…”
Section: Discussionmentioning
confidence: 99%
“…The recent development of reconstituted systems using highly purified proteins has enabled analyses of the detailed reaction mechanism of NER (7)(8)(9)(10). In yeast, some accessory or regulatory factors such as Rad7⅐Rad16 complex (11)(12)(13), ABF1 (14), and MMS19 (15)(16) have been reported to help mediate NER. The existence of such factors in humans, however, has not been clearly demonstrated.…”
Section: Nucleotide Excision Repair (Ner)mentioning
confidence: 99%
“…The Rad7 and Rad16 proteins also form a stable heterodimeric complex (16). Recent studies have demonstrated that these proteins are required for post-incision events during NER (15). Both proteins co-fractionate with recombinant Rad14 (Fig.…”
Section: His-tagged Rad14 Protein Complements Both the Uv Radiation Smentioning
confidence: 94%
“…2 Interestingly, extracts prepared from rad7, rad16, or rad23 strains, which exhibit moderate sensitivity to cell killing by UV radiation (5,6), are also defective in repair synthesis in vitro (14). Recent studies have shown that rad7 and rad16 mutant extracts are proficient in DNA damage-dependent incision both in vitro and in vivo but fail to excise the oligonucleotide fragment containing the DNA lesion (15). Hence, the Rad7 and Rad16 proteins, which interact with each other (16), appear to be required for post-incision events during NER.…”
mentioning
confidence: 99%